PARLAMENTTIŃ JÁMIYET TURAQLÍLÍǴÍN HÁM RAWAJLANÍWÍN TÁMIYINLEWDEGI ROLI - Bayrıeva, А.Q. (SCIENCE and SOCIETY, 2024)
This article examines some aspects of parliamentarism in the international community. The achievements of the new stage of development of Uzbekistan will be analyzed. The vital importance of public control is revealed and reforms to the development of the national parliament are explained.
Keywords: narodnoe obshchestvo; parliament; parliamentary zapret; parliamentary commission; inter-parliamentary sovmestnaya rabota; mestnyy Soviet; Oliy Majlis; Regulatory Chamber; Senate